Neuroendocrine response to GABA-B receptor agonism in alcohol-dependent individuals: Results from a combined outpatient and human laboratory experiment - Farokhnia, Mehdi (Neuropharmacology, 2018)
Gamma-aminobutyric acid (GABA), the main inhibitory neurotransmitter in the nervous system, plays an important role in biobehavioral processes that regulate alcohol seeking, food intake, and stress response. The metabotropic GABA-B receptor has been investigated as a potential therapeutic target for alcohol use disorder, by using orthosteric agonists (e.g., baclofen) and positive allosteric modulators. Whether and how pharmacological manipulation of the GABA-B receptor, in combination with alcohol intake, may affect feeding- and stress-related neuroendocrine pathways remains unknown. In the present randomized, double-blind, placebo-controlled study, thirty-four alcohol-dependent individuals received baclofen (30 mg/day) or placebo in a naturalistic outpatient setting for one week, and then performed a controlled laboratory experiment which included alcohol cue-reactivity, fixed-dose priming, and self-administration procedures. Blood samples were collected, and the following neuroendocrine markers were measured: ghrelin, leptin, amylin, glucagon-like peptide-1 (GLP-1), insulin, prolactin, thyroid-stimulating hormone, growth hormone, cortisol, and adrenocorticotropic hormone (ACTH). During the outpatient phase, baclofen significantly increased blood concentrations of acyl-ghrelin (p=0.01), leptin (p=0.01), amylin (p=0.004), and GLP-1 (p=0.02). Significant drug × time-point interaction effects for amylin (p=0.001) and insulin (p=0.03), and trend-level interaction effects for GLP-1 (p=0.06) and ACTH (p=0.10) were found during the laboratory experiment. Baclofen, compared to placebo, had no effect on alcohol drinking in this study (p’s≥0.05). Together with previous studies, these findings shed light on the role of the GABAergic system and GABA-B receptors in the shared neurobiology of alcohol-, feeding-, and stress-related behaviors.